Shifting focus in the therapeutics of immunobullous disease - Abhishek De; Asad Ansari; Nidhi Sharma; Aarti Sarda (Wolters Kluwer Medknow Publications, 2017)
Therapeutics of autoimmune bullous disease has seen a major shift of focus from more global immunosuppression to targeted immunotherapy. Anti CD 20 monoclonal antibody Rituximab revolutionized the therapeutics of autoimmune bullous disease particularly pemphigus. Though it is still being practiced off-label, evidences in the form of RCT and meta analysis are now available. Other novel anti CD 20 monoclonal antibodies like ofatumumab, veltuzumab, and ocrelizumab, tositumomab or obinutuzumab/GA101 may add to the therapeutic options in coming days. Beyond anti CD 20 monoclonal antibodies other options that show promise at least in select scenario are omalizumab, TNF inhibitors plasmapheresis and intravenous immunoglobulin. The present article will discuss the role of rituximab and other newer therapeutics in the treatment of autoimmune blistering disease, especially pemphigus and suggests their positions in the therapeutic ladder.